Differential cross sections and collision-induced rotational alignment in inelastic scattering of NO(X) by Xe - Brouad, M; Nichols, B; Hornung, B; Heid, C; Goddard, S; Jambrina, PG; Aoiz, FJ; Klos, J; Chadwick, H (AIP Publishing, 2020)
Fully Λ-doublet resolved differential cross sections and collision-induced rotational alignment moments have been measured for the NO(X)–Xe collision system at a collision energy of 519 cm−1 . The experiments combine initial quantum state selection, employing a hexapole inhomogeneous electric field, with quantum state resolved detection, using (1+1′ ) resonantly enhanced multiphoton ionization and velocity map ion imaging. The differential cross sections and polarization dependent differential cross sections are shown to agree well with quantum mechanical scattering calculations performed on ab initio potential energy surfaces [J. K los et al. J. Chem. Phys. 137, 014312 (2012)]. By comparison with quasi-classical trajectory calculations, quantum mechanical scattering calculations on a hard-shell potential, and kinematic apse model calculations, the effects of the attractive part of the potential on the measured differential cross sections and collision-induced rotational alignment moments are assessed.